Examining the Motivations, Concerns, and Perspectives of Medical Students Engaging in Neurological Surgery Research. (16th November 2020) - Barrios-Anderson, Adriel; Liu, David D; Snead, Jameson; Wu, Esther; Lee, David; Robbins, James; Aguirre, Jesus; Tang, Oliver Y; Garcia, Catherine M; Pucci, Francesco; Anderson, Matthew; Syed, Sohail; et al.
Abstract: INTRODUCTION: In a competitive landscape of neurosurgical training, research productivity has become increasingly important for preparation and application to residency. Successful applicants consistently have numerous "scholarly products" as published by the National Residency Match Program with recent work indicating that students publish, on average, 5 research papers by their intern year. Few reported studies have examined student perspectives on conducting research and garnering publications. METHODS: For two consecutive years (February 2019 and February 2020), medical students (n = 55) from around the United States and abroad presented original research at the Student Neurosurgical Research Conference (SNRC). Participants were administered a mixed-method survey designed to assess experiences and perspectives on engaging in neurosurgical research. Survey responses were analyzed independently by two researchers to assess for common themes and perspectives. RESULTS: Medical students engaged in research from various areas in neurosurgery including neuro-oncology, cerebrovascular, and functional neurosurgery. Students also engaged in all types of research work with "Basic/Bench Lab work" (38.5%) and "Chart Review" (23.1%) representing the majority of projects presented. When asked the main reasons for engaging in research most students cited "curiosity/interest, " and "residency application competitiveness." The majority (66%) of respondents reported experiencing anxiety/concern about research productivity "often" or "very often." Thematic analysis revealed that common sources of concern regarding research included 1) Having enough publications to match into residency, 2) Having enough time in medical school to engage in research, 3) Producing meaningful and high-quality research, and 4) Having limited time to meet research demands after clinical exposure to the field. CONCLUSION: Medical students engaging in neurosurgical research are highly motivated and engaged students. Scientific curiosity and pressure to prepare for competitive residency applications were primary motivators for students. Students experience anxiety due to time constraints in medical curricula and increasing demands for scholarly productivity.